Prevalencia y Severidad de Asma en Niños de Lima - VEGA-BRICEÑO, LUIS (2024)
The prevalence of asthma in children is increasing in many countries but such a trend has not been well defined in Peru. lt is important, therefore, to define this problem in Lima. This epidemiological study describes the prevalence and severity of asthmarelated symptoms in schoolchildren between 13 and 14 years old from Santiago de Surco, Lima, using the lnternational Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. A randomized sample was obtained from the USE-10 of Lima. A total of 3174 children were interviewed, but only 313 7 were included for analysis. lt was found a prevalence of asthma of 26%; 24% had been diagnosed with asthma by a medical professional at any time. Of the 814 who reported wheezing in the past 12 months, 70.8% reported exercise-induced asthma symptoms, and 42.8% dry night cough. Finally, 21.1% reported severe bronchial attacks. This data indicates that bronchial asthma is an illness of widespread prevalence in Lima and merits its mention as an important public health problem. Further studies should be aimed to identify the factors in the pathogenesis of asthma.